Immediate early transcription activation by salicylic acid via the cauliflower mosaic virus as-1 element. - Qin, X F (1994)
Transgenic tobacco plants carrying a number of regulatory sequences derived from the cauliflower mosaic virus 35S promoter were tested for their response to treatment with salicylic acid (SA), an endogenous signal involved in plant defense responses. beta-Glucuronidase (GUS) gene fusions with the full-length (-343 to +8) 35S promoter or the -90 truncation were found to be induced by SA. Time course experiments revealed that, in the continuous presence of SA, the -90 promoter construct (-90 35S-GUS) displayed rapid and transient induction kinetics, with maximum RNA levels at 1 to 4 hr, which declined to low levels by 24 hr. Induction was still apparent in the presence of the protein synthesis inhibitor cycloheximide (CHX). Moreover, mRNA levels continued to accumulate over 24 hr rather than to decline. By contrast, mRNA from the endogenous pathogenesis-related protein-1a (PR-1a) gene began to accumulate at later times during SA treatment and steadily increased through 24 hr; transcription of this gene was almost completely blocked by the presence of CHX. Further dissection of the region from -90 and -46 of the 35S promoter revealed that the SA-responsive element corresponds to the previously characterized activation sequence-1 (as-1). These results represent a definitive analysis of immediate early responses to SA, relative to the late induction of PR genes, and potentially elucidate the early events of SA signal transduction during the plant defense response.